Teachers’ Appreciation of Benefits and Shortcomings of Online and Blended Higher STEM Education - Iouliia Skliarova; Inês Meireles; Tatiana Tchemisova; Isabel Cação; Natália Martins (Education Sciences, 2023)
This paper is devoted to identifying online teaching strategies appropriate for blended and face-to-face higher STEM (Science, Technology, Engineering, and Mathematics) education. The study is inspired by the experience gained during the COVID-19 pandemic lockdown, which forced many higher education institutions worldwide to shift abruptly to distance education and try many new tools, teaching methods, and strategies. Some of these tools and strategies were abandoned as soon as the lockdown had been lifted and the institutions returned to their regular functioning, but some of them are bound to stay. Certainly, it would be beneficial to include the most valuable of the gained skills and competences in traditional on-campus and blended courses. The study is based on an online questionnaire, addressed to the STEM faculty of the University of Aveiro, Portugal (which is an example of an institution that used to provide face-to-face instruction), whose analysis permits to derive a number of important recommendations. The results are compared with our previous work, where the students’ perspectives were analyzed, and similarities and discrepancies in appreciation of the involved parties are highlighted. This work extends the body of knowledge about the impact of the COVID-19 pandemic on STEM education by examining the challenges and opportunities faced by teachers. The recommendations derived contribute to improving the learning outcomes of online STEM education in many similar institutions.